2017
DOI: 10.3390/ijms18061318
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Analysis of Vitamin D Receptor Status of Circulating Tumor Cells (CTCS) in Breast Cancer: From Cell Models to Metastatic Patients

Abstract: The Vitamin D receptor (VDR) expressed in normal breast tissue and breast tumors has been suggested as a new prognostic biomarker in breast cancer (BC). Besides, increasing evidence supports the view that the detection of circulating tumor cells (CTCs) predicts outcome in early and metastatic BC. Consequently, an evaluation of VDR expression in the CTCs of BC patients may allow optimization of their treatment. As an attempt to profile and subtype the CTCs of metastatic patients, we established an innovative fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Vitamin D and the VDR have become a complex story with an evolving landscape, especially in the last few decades [4,5,9,12,18,19,44,45,46,47,48]. Deuster et al reviewed the importance of Vitamin D and its receptor in the pathogenesis of certain types of cancer such as colorectal, lung but mainly gynecological cancers, where they found the VDR to be upregulated, indicating its relevance for cancer etiology [46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vitamin D and the VDR have become a complex story with an evolving landscape, especially in the last few decades [4,5,9,12,18,19,44,45,46,47,48]. Deuster et al reviewed the importance of Vitamin D and its receptor in the pathogenesis of certain types of cancer such as colorectal, lung but mainly gynecological cancers, where they found the VDR to be upregulated, indicating its relevance for cancer etiology [46].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these regimes are currently, according to National Comprehensive Cancer Network (NCCN) guidelines, an indispensable part of the adjuvant therapy for women with hormone receptor-positive (HR+) BC [2,3]. Clinical studies have confirmed that a high HR expression, such as estrogen receptor (ER), progesterone receptor (PR), and vitamin D receptor (VDR), increases the course of the disease [4,5,6,7,8]. In this study, we decided to further investigate the above-mentioned HR expressions, all being nuclear receptors, activated by their steroid hormones and being important targets for both prevention and treatment of BC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D deficiency and the low tumor expression level of VDR are correlated with aggressive breast cancer characteristic [18][19][20]. Also preliminary analysis of breast cancer circulating tumor cells suggests VDR as a potential prognostic biomarker [21]. The data showing promotion of tumor growth and metastasis via vitamin D deficiency are presented also using xenografts of human breast cancer cell lines [22] and allografted mouse tumors [23][24][25].…”
mentioning
confidence: 98%
“…Beside ER and PR, other nuclear receptors (NR) play a role in BC, as we and other have reported earlier (Bock et al 2014;Ditsch et al 2012;Doan et al 2017;Heublein et al 2017;Jalaguier et al 2017;Jeschke et al 2019;Shao et al 2020aShao et al , 2020bZhang et al 2017). Liver X receptors (LXRs) belong to the NR superfamily (Wang and Tontonoz 2018) and have two isotypes, LXRα and LXRβ (encoded by the NR1H3 and NR1H2 gene, respectively).…”
Section: Introductionmentioning
confidence: 94%